Syeikh Ahmad bin Muhammad Zain bin Mustafa Al- Fatani: peranan dalam bidang politik dan pendidikan di alam Melayu abad ke 20 = Syeikh Ahmad bin Muhammad Zain bin Mustafa Al-Fatani: The role in politics and education in the Malay world in the 20th century - Yaacob, Adli; Yaacob, Solehah@Nik Najah Fadilah; Yaacob, Hakimah; Yaacob, Bahruddin (Global Academic Excellence, 2022)
Sheikh Ahmad is a descendant of a preacher from Yemen (Hadramout) who has settled in Pattani. He is one of the Islamic scholars 'who has brought Pattani to the pinnacle of knowledge and it is not surprising that he is considered as one of the reknown scholars in Makkah al-Mukarramah at par with other leading figures. Sheikh Ahmad has played a role that is no less important when compared to Sheikh Daud who was a mentor to him. It is not an overstatement to say that Sheikh Ahmad to Sheikh Daud is like Aristotle to Plato. The scope of his role includes the field of knowledge studies, writing, translation and all dakwah efforts that are taken up in the name of Islam. Despite having left Pattani for Makkah al-Mukarramah for a long time, he still did not forget his homeland.